1995
DOI: 10.2165/00003495-199549060-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cefixime

Abstract: Cefixime is an orally active third generation cephalosporin with in vitro antibacterial activity against most important lower respiratory pathogens. The drug is active against Haemophilus influenzae, Moraxella catarrhalis and penicillin-susceptible Streptococcus pneumoniae but not Staphylococcus aureus. Cefixime has a long elimination half-life (3 hours compared with 0.5 hours for cefaclor and 1.5 hours for cefalexin), which allows once daily administration. Several trials have established the clinical efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…All isolates included in the study were grouped into inducible or non-inducible Enterobacteriaceae and non-fermenters, as observed in Table 2, and tested for susceptibility to each of the three antibiotics. Cefixime has been deemed less effective towards nonfermenters and members of inducible Enterobacteriaceae in a study by Markham et al [15] and is similarly observed in our study as only scarce susceptibility of the pathogens to Cefixime was observed in Table 3.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…All isolates included in the study were grouped into inducible or non-inducible Enterobacteriaceae and non-fermenters, as observed in Table 2, and tested for susceptibility to each of the three antibiotics. Cefixime has been deemed less effective towards nonfermenters and members of inducible Enterobacteriaceae in a study by Markham et al [15] and is similarly observed in our study as only scarce susceptibility of the pathogens to Cefixime was observed in Table 3.…”
Section: Discussionsupporting
confidence: 83%
“…Cefixime is an oral third-generation cephalosporin, commonly used in the treatment of important lower respiratory tract infections [5]. In some non-comparative studies, the efficacy of Cefixime was found to be similar to Cefaclor, Cefalexin, Amoxicillinclavulanic acid, and Cefuroxime axetil in patients suffering from LRTIs [15]. Comparative studies have suggested Cefixime be equally efficacious as intravenous Ceftriaxone, oral Cefalexin, Amoxicillin-clavulanic acid, and Clarithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…The reported bioassays methods of hTNF-␣ measurements lack sensitivity and specificity, besides of being time consuming in comparison to immunoassay techniques. On the other hand, the sensitivities of the present reported hTNF-␣ enzyme immunoassay methods are in the range of 1 pg/ml (17)(18)(19)(20)(21). To enhance the sensitivity of the assay, we developed an enzyme immunosorbent assay with biotin…”
Section: Discussionmentioning
confidence: 81%